Analisis reaksi pasar saham terhadap pengumuman lockdown Covid – 19 lima negara wilayah Asia Tenggara - Eka Yuning Pratiwi; Isbandini Veterina; Basuki Toto Rahmanto (LPMP Imperium, 2022)
The capital market is susceptible to changes or events happening inside or outside the country. Changes in the capital market will affect them directly or indirectly to the economy. The announcement of COVID – 19 lockdown is one of the major impacts on the capital market nowadays. This study aims to determine whether there are significant differences in returns before and after the announcement of the COVID – 19 lockdown in five countries in the Southeast Asia region. The five countries were selected based on the fifth highest population (Indonesia, Philippines, Vietnam, Thailand, and Myanmar). The period of observation is 90 days, and the forecast period is 21 days; the window period is ten days before and ten days after the announcement. The results showed that there was no significant difference in returns before and after the announcement in five countries in the Southeast Asia region.